Advice strategies made by native Speakers of English and native Vietnamese Learners of English - Nguyễn, Thị Quỳnh Hoa (Viện Ngôn ngữ học - Viện Hàn lâm Khoa học xã hội Việt Nam, 2023)
The article focuses on the Advice strategies made by Native Speakers of English and Native Vietnamese learners of English. The aim of the study is to discuss the similarities and differences between advice strategies chosen by the native speakers of English and the native Vietnamese learners of English. The article also aims to find out how the social factors affect the selection of advice strategies in both languages. The data collected from the given situations in the questionnaire delivered to the sixty five English subjects and the same number of Vietnamese subjects will be analyzed in terms of the selection of advice strategies in connection with social factors, and the levels of directness - direct advice, conventionally indirect advice and non-conventionally indirect advice. The results have revealed that the Vietnamese respondents appear to be more direct in giving advice than the native English subjects especially in higher power situations. Moreover, Social Distance is also supposed to have influence on the choice of advice strategies in English and Vietnamese.